2006
DOI: 10.1001/archpedi.160.12.1269
|View full text |Cite
|
Sign up to set email alerts
|

Youth

Abstract: A comprehensive health care-based lifestyle intervention can effectively improve dietary intake and increase bone mineral gains in adolescent girls. To our knowledge, this study is the first to significantly improve bone mass in adolescent girls in a non-school-based intervention. Trial Registration ClinicalTrials.gov Identifier: NCT00067600.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“… 31 For example, in a study reported by Debar et al (2006), adolescent girls' recordings of their diet and exercise goals and achievements were regularly shared with their peer group and their coach. 53 In another study reported by Wennberg et al (2010), participants in a telephone-based care management intervention signed a behavioral contract with their wellness coaches, and had access to a computer program that tracked progress toward goals through the intervention. 54 An additional 5% of articles described coaching in which accountability was partially built in.…”
Section: Resultsmentioning
confidence: 99%
“… 31 For example, in a study reported by Debar et al (2006), adolescent girls' recordings of their diet and exercise goals and achievements were regularly shared with their peer group and their coach. 53 In another study reported by Wennberg et al (2010), participants in a telephone-based care management intervention signed a behavioral contract with their wellness coaches, and had access to a computer program that tracked progress toward goals through the intervention. 54 An additional 5% of articles described coaching in which accountability was partially built in.…”
Section: Resultsmentioning
confidence: 99%
“…A further prospective study found a significantly higher bone mass in children with a high consumption of dark-green and deep-yellow vegetables [212]. DeBar et al [213] conducted a randomised study over 2 years, in which 228 adolescent girls (in the age between 14 and 16 years) were asked to increase their physical activity and to improve their diet, including an increased consumption of vegetables and fruit. Compared with the control group, the girls in the intervention group had a significantly higher bone density at the spine and the femoral neck.…”
Section: Judgement Of the Evidence Regarding Individual Diseasesmentioning
confidence: 99%
“…Education programs had an emphasis on healthy lifestyle habits (diet and physical activity). Educational Mix 24 2 weeks 24-h recall Yes DeBar, et al 2006 [ 37 ] Behavioral intervention (bimonthly group meetings, quarterly coaching telephone calls, and weekly self-monitoring) designed to improve diet and increase physical activity. Educational Mix 96 1 week 24-h recall Yes DeBar, et al 2009 [ 38 ] Participants were urged to consume 1350 mg/day of calcium (four glasses of milk a day or the equivalent) and eight servings of fruits and vegetables, as well as to participate in exercise.…”
Section: Resultsmentioning
confidence: 99%